2014
DOI: 10.1016/j.smim.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new STATe: The role of STATs in mitochondrial function

Abstract: Signal Transducers and Activators of Transcription (STATs) have been studied extensively and have been associated with virtually every biochemical pathway. Until recently, however, they were thought to exert these effects solely as a nuclear transcription factor. The finding that STAT3 localizes to the mitochondria and modulates respiration has opened up a new avenue through which STATs may regulate the cell. Recently, other members of the STAT family (STAT1, STAT2, STAT5, and STAT6) have also been shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 78 publications
4
139
0
Order By: Relevance
“…3A), probably resulting in biased STAT3 activation. A recent study describes the mitochondrial trafficking of caveolin-1 and STAT3 (Meier and Larner 2014). The major portion of STAT3 that associates with nonraft fractions as shown in Figure 3 may account for the mitochondrial localization of STAT3.…”
Section: Discussionmentioning
confidence: 89%
“…3A), probably resulting in biased STAT3 activation. A recent study describes the mitochondrial trafficking of caveolin-1 and STAT3 (Meier and Larner 2014). The major portion of STAT3 that associates with nonraft fractions as shown in Figure 3 may account for the mitochondrial localization of STAT3.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have shown that STAT3 can localize to the mitochondrion, where it promotes oxidative phosphorylation and membrane permeability (Figure 1). This effect is dependent on serine but not tyrosine phosphorylation and is thought to be relevant in settings where cellular respiration is altered, such as cellular stress and cancer (58). All other STATs (save STAT4) have now been detected in the mitochondrion but their function within this organelle has not been rigorously assessed (58).…”
Section: Non-canonical Aspects Of Jak/stat Signalingmentioning
confidence: 99%
“…This effect is dependent on serine but not tyrosine phosphorylation and is thought to be relevant in settings where cellular respiration is altered, such as cellular stress and cancer (58). All other STATs (save STAT4) have now been detected in the mitochondrion but their function within this organelle has not been rigorously assessed (58). Another intriguing ‘geographical’ deviation involves Jak2, which has been shown to mediate p-Tyr of nuclear histones (59).…”
Section: Non-canonical Aspects Of Jak/stat Signalingmentioning
confidence: 99%
“…Phosphorylation at Tyr705 (pTyr705), catalyzed by Janus kinases (JAK) and other tyrosine kinases, induces STAT3 dimerization through the interaction of the SH2 domain (SH2D), nuclear accumulation, and target gene transcription (1,3,4). Emerging evidence indicates that STAT3 also localizes to mitochondria and controls mitochondrial functions (2,(5)(6)(7). Mitochondrial localized STAT3 (mSTAT3) is critical for survival of RAStransformed mouse embryo fibroblasts (MEF) under glucosestarvation, reflecting a specific dependency of cancer cells on mitochondria in certain conditions (6).…”
Section: Opb-51602mentioning
confidence: 99%